Living on a Time Bomb: Local Negotiations of Oil Extraction in a Mexican Community - Svenja Schöneich (Berghahn Books, 2022)
Providing a holistic understanding of extensive oil extraction in rural Mexico, this book focuses on a campesino community, where oil extraction is deeply inscribed into the daily lives of the community members. The book shows how oil shapes the space where it is extracted in every aspect and produces multiple uncertainties. The community members express these uncertainties using the metaphor of the time bomb. The book shows how they find ways to "live off the time bomb" by using mechanisms of short-term coping and long-term adaptation and thus, developing the capability to determine their lives despite the ever-changing challenges.
Keywords: 300; Social Science; Sociology; Rural; Business & Economics; Industries; Natural Resource Extraction; Social Science; Anthropology; Cultural & Social